Ecological Aspects and Regeneration of Sugar Palm in the Sasak Community Gardens of Kekait Village, West Nusa Tenggara, Indonesia - Anggit Haryoso; Ervizal A. M. Zuhud; Agus Hikmat; Dudung Darusman (Institut Pertanian Bogor (IPB University), 2020)
Sugar palm (Arenga pinnata Merr.) is one kind of palm that has multiple benefits on the Sasak community of Kekait Village. Despite its benefit, the information of sugar palm is barely unknown since the farmers depend on the nature cultivation. The Research aimed to analyze ecological aspects: composition, structure, the vegetation distribution, which includes the rate of regeneration and spatial distribution of sugar palm in the Sasak community garden in Kekait Village, West Lombok Regency, West Nusa Tenggara Province. The methods employed in the research is a single plot method with randomly selected. Obtained data are being analyzed quantitatively and qualitatively. The research successfully identified 68 species of 30 families plant. The majority of species are Meliaceae and Anacardiaceae families. The highest IVI from seedlings, saplings, poles, and trees are A. pinnata (52.09%), T. cacao (22.72%), G. gnemon (91.49%), D. zibethinus (80.19%). The vegetation structures showed a well-developed structure. The vegetation distribution in the farmers' garden indicated a clustered pattern within three strata; B, C, and D strata. The regeneration level of A. pinnata categorized as fair sustainable with a clustered distribution pattern. The pattern is affected by the reproduction and distribution of A. pinnata seeds which carried out by Rinjani weasel (Paradoxurus hermaphroditus rinjanicus).